Kritik Sastra Feminis pada Citra Perempuan Kontrafeminis dalam Novelisasi Film Yuni - Hayya Nafia; Trie Utari Dewi (BELAJAR BAHASA: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2022)
In real life, women face male domination as well as counterfeminist women who do not support the empowerment of fellow women so that stereotypes of women grow in patriarchal society. The depiction of the counterfeminist woman is present in the novelization of Yuni's film. This study aims to carry out feminist literary criticism on the image of counterfeminist women in the novelization of Yuni's film based on Djajanegara's theory. The theory is derived from an ideological feminist critique that interprets interpretation as a researcher as a female reader of images, stereotypes, and reasons for being seen as such. The method used is descriptive qualitative through literature study analysis techniques, data reduction, data presentation, and conclusions on quotes, dialogues and paragraphs as a source of research data. The results show that there are two images of counterfeminist women that build the existence of female stereotypes, including: [1] self-image of counterfeminist women related to the stigmatization of virginity, the moral burden of taking care of children, and the inferiority of women behind polygamy and [2] social images related to the slogan of domestic women "Well, Kitchen, Mattress”, early marriage for young women, and the stigma of widowed women in Yuni's film novelization.